Rolling Thunder - Messner, Kate (Scholastic Press, 2017)
Told in rhyming text, a boy accompanies his grandfather on the Rolling Thunder Ride for Freedom, a demonstration in Washington, DC, on Memorial Day that pays tribute to American veterans.